2018
DOI: 10.1016/j.jpsychires.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect is more strongly associated with suicidal thinking among suicidal patients with borderline personality disorder than those without

Abstract: Patients suffering from borderline personality disorder (BPD) are at elevated risk for suicidal thoughts and behaviors (STBs), but this well-described and clinically important association is not well-understood. Prior research suggests that STBs often function as an attempt to escape aversive affect, and that people with BPD experience stronger emotion reactivity and greater discomfort with emotion than those without BPD. Here, we tested whether negative affective states are more likely to predict suicidal tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 16 publications
(17 reference statements)
0
24
1
Order By: Relevance
“…These factors were not considered explicitly in the other studies, and their respective influence remains unclear. Future research is warranted: one study recently found that personality disorders play a role in explaining countertransference towards suicidal patients (Michaud et al, 2020) and another article showed that negative affects impact suicidal patients more when they suffer from a personality disorder (Mou et al, 2018), and such an interaction is probable regarding countertransference.…”
Section: Specific Countertransference Towards Suicidal Patientsmentioning
confidence: 99%
“…These factors were not considered explicitly in the other studies, and their respective influence remains unclear. Future research is warranted: one study recently found that personality disorders play a role in explaining countertransference towards suicidal patients (Michaud et al, 2020) and another article showed that negative affects impact suicidal patients more when they suffer from a personality disorder (Mou et al, 2018), and such an interaction is probable regarding countertransference.…”
Section: Specific Countertransference Towards Suicidal Patientsmentioning
confidence: 99%
“…Borderline personality disorder (BPD) is characterized by a pervasive pattern of emotion dysregulation, hyper‐intensity affect, unstable interpersonal relationships, and impulsive behavior (Gunderson, Herpertz, Skodol, Torgersen, & Zanarini, 2018; Leichsenring, Leibing, Kruse, New, & Leweke, 2011), which is a common and serious psychiatric disorder with an estimated prevalence of 0.7–5.9% in the general population, 10% in psychiatric outpatients and 15–25% in inpatients (Gunderson et al, 2018; Leichsenring et al, 2011). Long‐term follow‐up research confirmed that it's more difficult for BPD patients to attain and maintain the sustained remissions and recoveries than patients with other personality disorders (Gunderson et al, 2011; Mou et al, 2018). BPD is also regularly comorbid with axis I and other axis II disorders, especially mood disorders, anxiety disorders, and disorders related to substance abuse (Leichsenring et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, a recent set of findings implies that sleep disruption potentially charts the progression of BPD symptom severity and suicidality by impairing emotional functioning (Balestrieri et al, 2006;Fleischer et al, 2012;Grove et al, 2017;Lereya et al, 2017;Morales-Muñoz et al, 2020;Sjostrom et al, 2009;Wojnar et al, 2009;Wall et al, 2020). Understanding the clinical significace of sleep for affective dysregulation is particularly relevant to BPD, because cumulative evidence implies that the within-person association between negative affective states and the severity of suicidal ideation is particularly pronounced in BPD (Kaurin et al, 2020;Links et al, 2007;Mou et al, 2018).…”
Section: Sleep and Next-day Negative Affect And Suicidal Ideation In mentioning
confidence: 99%